Clinical patterns and genomic profiling of recurrent 'ultra-low risk' endometrial cancer. Issue 6 (5th May 2020) - Stasenko, Marina; Feit, Noah; Lee, Simon S K; Shepherd, Cassandra; Soslow, Robert A; Cadoo, Karen A; Alektiar, Kaled; Da Silva, Edaise M; Martins Sebastião, Ana Paula; Leitao Jr, Mario M; Gardner, Ginger; Selenica, Pier; et al.
Abstract : Objective: Despite good prognosis for patients with low-risk endometrial cancer, a small subset of women with low-grade/low-stage endometrial cancer experience disease recurrence and death. The aim of this study was to characterize clinical features and mutational profiles of recurrent, low-grade, non-myoinvasive, 'ultra-low risk' endometrioid endometrial adenocarcinomas. Methods: We retrospectively identified patients with International Federation of Gynecology and Obstetrics (FIGO) stage IA endometrioid endometrial cancers who underwent primary surgery at our institution, between January 2009 and February 2017, with follow-up of ≥12 months. 'Ultra-low risk' was defined as FIGO tumor grade 1, non-myoinvasive, and lacking lymphovascular space invasion. Tumor-normal profiling using massively parallel sequencing targeting 468 genes was performed. Microsatellite instability was assessed using MSIsensor. DNA mismatch repair (MMR) protein proficiency was determined by immunohistochemistry. Results: A total of 486 patients with ultra-low risk endometrioid endometrial cancers were identified: 14 (2.9%) of 486 patients developed a recurrence. Median follow-up for non-recurrent endometrioid endometrial cancers: 34 (range 12–116) months; for recurrent endometrioid endometrial cancers: 50.5 (range 20–116) months. Patients with recurrent disease were older, had lower body mass index, and were most commonly non-White (p=0.025, p<0.001, and p<0.001, respectively). Other clinical characteristics did not differ. MMR immunohistochemistry was obtained for 211 (43%) tumors: 158 (75%) MMR-proficient and 53 (25%) MMR-deficient. Primary tumors of 9 recurrent and 27 non-recurrent endometrioid endometrial cancers underwent mutational profiling. Most were microsatellite stable (6/9, 67% recurrent; 25/27, 93% non-recurrent). Recurrent PTEN and PIK3CA mutations were present in both groups. Exon 3 CTNNB1 hotspot mutations were found in 4/9 (44%) recurrent and 8/27 (30%) non-recurrent (p=0.44). Conclusions: Patients diagnosed with ultra-low risk endometrioid endometrial cancers have an overall excellent prognosis. However, in our study, 2.9% of patients with no identifiable clinical or pathologic risk factors developed recurrence. Further work is warranted to elucidate the mechanism for recurrence in this population.